Transcultures - National Museum of Contemporary Art, Athene; Balka, Miroslaw; Fritsch, Katharina; Geers, Kendell; Hadjimichalis, George; Hatoum, Mona; Hill, Gary; Kafetsi, Anna; Kimsooja; Menick, John; Neshat, Shirin; Raad, Walid; et al. (Athens : EMST (National Museum of Contemporary Art) Athens, 2004)
Balka, Miroslaw ; Fritsch, Katharina ; Geers, Kendell ; Hadjimichalis, George ; Hatoum, Mona ; Hill, Gary ; Jacir, Emily ; Kimsooja ; Kounellis, Jannis ; Laib, Wolfgang ; Neshat, Shirin ; Raad, Walid ; Stratou, Danae ; Suh, Do-Ho ; The Atlas Group ; Tsoclis, Costas ; Varotsos, Costas ; Viola, Bill
biog., ind. tent., gr. tent., bibliog. p. 124-148
The catalogue was published on the occasion of the exhibition "Transcultures" in Athens, 06.07.2004 - 31.12.2004
Engels
Grieks
boek